Service Quality Evaluation of Transfer Facilities in High-Speed Railway Stations Based on Interval Valued Linguistic Multi-Criteria Decision-Making - Shang WU; Shaozhi HONG; Zeling WANG; Zhiyuan SHI; Jiayu ZANG (Promet (Zagreb), 2025)
High-speed railway stations are critical in facilitating seamless connections between different transportation modes. However, challenges such as mismatched transfer capacities, inefficient mode connections and excessive passenger transfer distances and times hinder the efficiency of these stations, impeding overall transport system development. This paper addresses the need for effective evaluation of transfer facility service quality within high-speed railway stations, providing a foundation for optimising these facilities. Leveraging interval-valued linguistic term sets (IVLTSs), this study develops interval-valued linguistic multi-criteria decision-making (IVL-MCDM) methods to assess service quality while accounting for uncertainty in evaluation indicators and attribute weights. We introduce new dominance degrees to enhance the reliability of evaluations, ensuring consistency in assessing transfer facility service quality. The proposed methods are demonstrated through a case study, highlighting their effectiveness and superiority over traditional IVL-MCDM approaches, particularly in maintaining consistent evaluation information.